Fundamentals of Entrepreneurship (ENT300) : Cachet & Co. / Seri Nazirah Athanazir... [et al.] - Athanazir, Seri Nazirah; Baba@Sumardee, Nur Ameera; Wan Salahudin, Sharifah Nur Mastura; Ismadi, Siti Nur Athirah; Azman, Nur Aimi 'A ilah (2014)
A marketing plan may be a part of an overall business plan. A solid marketing strategy is the foundation of a well written marketing plan. While a marketing plan contains a list of actions, a marketing plan without a sound strategic foundation is of little use.